Design of narrowband tunable filter for LTE Band 5 - Sabir, M. K.S.K.; Mohd. Isa, Farah Nadia; Mohd Marzuki, A.S.; Mohd. Ramli, Huda Adibah; Ruslan, Ahmad Alhadi (IEEE, 2019)
The objective of this project is to design and develop a tunable bandpass filter for LTE Band 5 that work within the frequency range of 869 MHZ - 894 MHz. The filter characteristic that being tuned in this design is the center frequency while the bandwidth remains the same. The tunability of the design is electronically controlled by adjusting the capacitance value in the filter network. The design is being constrict by the currently available lumped element component in the market. The design methodology of the tunable filter are being introduced in this project. Several thesis and article regarding RF microwave filter design are reviewed before coming up with the methodology for the design.